Stochastic simulation of the January 24, 2020 Elazığ,-Sivrice earthquake - Acar, Şükran. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2023., 2023)
This thesis focuses on the application of stochastic ground motion simulation methodology to the 24 January 2020 Mw 6.8 Elazığ-Sivrice earthquake, which occurred on the P¨ut¨urge segment of the East Anatolian Fault in Turkey. In this context, the dynamic corner frequency-based stochastic finite fault method was used to simulate the ground motion fields generated by the 24 January 2020 Elazığ-Sivrice earthquake earthquake. Input parameters for the simulations are derived from regional sources and seismic parameters to ensure the reliable production of synthetic ground motions. The model parameters are evaluated by comparing the real records of the Elazı˘g- Sivrice earthquake with synthetic records and preferred models are selected accordingly. Moreover, the synthetic records have been compared with regionally suitable ground motion models (GMMs). The stochastic ground motion simulation methodology is used together with the extended fault model, evaluating both random and earthquake specific slip distribution options. Alternative models or values are considered for the stress drop, geometric spreading, Q and duration models as well as for site amplification. A combination of models that yield the lowest error terms both in frequency and time domain parameters is proposed as the preferred model for this study. As a result of this study, it is seen that the simulations of the Elazı˘g- Sivrice (Mw 6.8) event give reasonable results for frequency ranges higher than 1 Hz and the determined parameters can be further developed and used as input to other studies evaluating seismic hazards in related regions.
Keywords: Stochastic systems.; Elazığ Earthquake, Turkey, 2020.